2012
DOI: 10.1089/thy.2010.0406
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Patients Treated with 131I: Radiation Dose to Relatives After Discharge from the Hospital

Abstract: With our current practice, radiation doses to relatives are low and well below international recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
3
0
4
Order By: Relevance
“…This result is compatible with that of another study which showed the mean radiation dose delivered to family members was similar with either rhTSH or thyroid hormone withdrawal. [ 14 ] In addition, we noted that renal function was also not a critical factor for the amount of radiation exposure to the household environment from patients with thyroid cancer after RAI therapy. Furthermore, whether the patients were receiving their initial RAI therapy or not was not associated with the amount of radiation exposure from the patients to the household environment, although there could possibly be more radiation exposure from patients receiving their first RAI therapy due to greater 131 I uptake of the remnant after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…This result is compatible with that of another study which showed the mean radiation dose delivered to family members was similar with either rhTSH or thyroid hormone withdrawal. [ 14 ] In addition, we noted that renal function was also not a critical factor for the amount of radiation exposure to the household environment from patients with thyroid cancer after RAI therapy. Furthermore, whether the patients were receiving their initial RAI therapy or not was not associated with the amount of radiation exposure from the patients to the household environment, although there could possibly be more radiation exposure from patients receiving their first RAI therapy due to greater 131 I uptake of the remnant after surgery.…”
Section: Discussionmentioning
confidence: 96%
“…L'instauration d'une période de restriction, n'est donc pas fortuite, au contraire elle est nécessaire pour minimiser l'exposition des proches pendant les jours qui suivent immédiatement la sortie de l'hôpital, là où les débits de doses sont encore relativement élevés. En effet, ceci peut être constaté par des mesures directes sur les proches du patient qui, dans des conditions similaires à celles de notre étude et en respectant les consignes de radioprotection (Remy et al, 2012), ont reçu de faibles doses de l'ordre de 51 mSv en 7 jours. Et bien entendu, si le patient ne reprend des contacts normaux avec ses proches qu'au terme de la période conseillée, les doses qu'il est susceptible de délivrer à son entourage seraient très significativement plus faibles.…”
Section: Discussionunclassified
“…Las clasificaciones surgidas en los años 80 como AMES, AGES, MACIS, MSKCC, TNM (que consideraban el tamaño del tumor, la presencia de metástasis regionales y/o a distancia, la extensión por fuera del órgano, la edad, el grado tumoral, etc.) centraban su predicción en el factor mortalidad (14,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) . Sin embargo, los estudios con seguimientos a largo plazo han demostrado que la mortalidad en la mayoría de los tumores tempranos no supera el 3-5% y que el desenlace más importante para un paciente con cáncer de tiroides es la recurrencia, la cual no se consideró en el diseño de estos índices.…”
Section: Estadificación Dinámica Del Riesgounclassified
“…La publicación del ensayo francés dirigido por él (28) y las del ensayo británico dirigido por Ujjal Mallick (29) , donde se buscaba evaluar la efectividad de la TSH recombinante humana, mostró con claridad que al momento de la ablación 23-59% de los pacientes con tumores tempranos tenían valores de tiroglobulina menores de 2 ng/ml, demostrando que en estos pacientes la ablación no tendría ningún efecto clínico importante. De otro lado, los dos ensayos demostraron que cuando la ablación es necesaria, dosis menores (30 mci) son igualmente efectivas para obtener una negativización de la tiroglobulina, lo que se traduce en la posibilidad de realizar ablaciones en condiciones ambulato- rias sin riesgo para la sociedad, con mayor comodidad para el paciente que no requiere las condiciones de aislamiento necesarias cuando se usan dosis más altas y en un uso racional de las ya escasas unidades de aislamiento para terapia con yodo radiactivo disponibles en el mundo (30) . Se espera entonces que las guías mantengan las recomendaciones de 2009 y las extiendan a los pacientes con tumores de hasta 4 cm e incluso que sugieran el uso restringido en pacientes clasificados como de riesgo intermedio y consideren su uso sólo para casos de ganglios centrales positivos pero con invasión extracapsular.…”
Section: Disminución De Las Indicaciones Y De La Dosis De Ablación Con Yodo Radiactivounclassified